REPRESENTASI TOLERANSI KEBERAGAMAN UMAT BERAGAMA DALAM FILM GOOGLE NGULIK RAMADHAN-SATU DALAM KITA (ANALISIS SEMIOTIKA JOHN FISKE) - Fiqie Lavani Melano; Freddy Yusanto (Dialektika, 2019)
Indonesia is an archipelagic country full of wealth and diversity of cultures, races, ethnic groups, beliefs, religions, and many others. Although full of cultural diversity, Indonesia remains one according to its slogan, Bhineka Tunggal Ika which means "though different but still one". Seeing through the phenomenon that occurs at this time, Indonesia, which has six religions that had functioned as a unifying not infrequently become an element of conflict. Some religious people feel that their religion is the most correct, the most kind and the most acceptable, with that thought followed by the ego of each individual, then there is a conflict between religious people. Researchers are interested in how religious diversity values and tolerance are represented in the movie Google Ngulik Ramadhan - Satu Dalam Kita. With the current phenomenon, researchers feel the audience needs to apply the values of tolerance to life. This study uses a qualitative approach by using semiotics analysis to analyze the object under study. The data analysis technique is based on John Fiske's theory of "The Codes of Television". From the results of this study can be concluded that the researchers analyze that there is an ideology behind this mini drama. In the movie Google Ngulik Ramadan - One In We pluralism seen trying to be represented by Rudi Soedjarwo as a director. Pluralism is how sincerity in every human being to accept the diversity that exists.